Dentição do Chrysocyon brachyurus (Illiger,1815) e sua relação com a dieta - Nalla, Susana Faria (2017)
The study of dentition pattern of wild animals allows obtaining information about the anatomy, physiology, behavior and feeding of the species. The present study aimed to compare the dentition of maned wolf, Chrysocyon brachyurus, with the domestic dog, Canis lupus familiaris, as well as to describe the dental anatomy peculiarities of the species related to its diet. Eleven adult male C. brachyurus skulls were collected from highways in the Triângulo Mineiro, MG, Brazil. They are belonged to the collection of the Laboratory for Teaching and Research in Wild Animals of the Federal University of Uberlândia. The skulls were macerated for soft tissue removal and visualization of the bones. Afterwards, photos were taken, a description of the dental anatomy of the specimens was carried out, compared with a domestic dog skull and the literature about the maned wolf diet. In relation to the number of teeth, most of the skulls of Chrysocyon brachyurus presented 42 teeth with shape, occlusion pattern and arrangement similar to those of C. lupus familiaris. However, in three specimens (27.27%) the absence of the madibula second molar was observed. In one skull this finding occurred bilaterally, and in the others, only in one antimer. It was also observed that the dentition pattern of Chrysocyon brachyurus reflects the characteristic of the omnivorous diet of the animal.